On vertex-stabilizers of bipartite dual polar graphs - Miklavič, Štefko (Ars mathematica contemporanea, 2010)
Let ?$X,Y$? denote vertices of a bipartite dual polar graph, and let ?$G_X$? and ?$G_Y$? denote the stabilizers of ?$X$? and ?$Y$? in the full automorphism group of this graph. In this paper, a description of the orbits of ?$G_X \cap G_Y$? in the cases when the distance between ?$X$? and ?$Y$? is 1 or 2, is given.
Keywords: grafi; grupe; matematika